Management of a taxi services company through use of GPS positioning and GPRS data transfer - Belcheva Dragneva, Nikolina (Univerzita Pardubice, 2010)
The article describes methods of management and use of the GPS systems in taxi companies through application of advanced information technologies, such as GPS positioning and GPRS data transfer. All these systems are united in an integrated solution – taxi information system (TIS), which includes all aspects of the activities of the taxi companies.
Keywords: GPS positioning; GPRS data transfer; TIS taxi information system; taxi services